2012
DOI: 10.1007/s00268-012-1655-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triclosan‐Coated Sutures on the Incidence of Surgical Wound Infection After Lower Limb Revascularization Surgery: A Randomized Controlled Trial

Abstract: The use of triclosan-coated sutures does not reduce the incidence of SWI after lower limb vascular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 27 publications
1
54
0
3
Order By: Relevance
“…The study showed that triclosan-coated sutures do not reduce the risk of SWI (13). Another randomized trial with 374 patients reported that legwound closure with triclosan-coated sutures does reduce the SWI rate in cAbg patients after open vein harvesting (62).…”
Section: Preventionmentioning
confidence: 97%
See 3 more Smart Citations
“…The study showed that triclosan-coated sutures do not reduce the risk of SWI (13). Another randomized trial with 374 patients reported that legwound closure with triclosan-coated sutures does reduce the SWI rate in cAbg patients after open vein harvesting (62).…”
Section: Preventionmentioning
confidence: 97%
“…Furthermore, obesity has increased the risk of SWI after peripheral artery surgery in other studies with smaller number of patients with an OR varying between 1.7 and 6.08 (11,13,23,25,39). In addition, morbid obesity (body mass index (bmI) ≥ 40 kg/m 2 ) has been found to be an independent risk factor for SWI after open aortic aneurysm repair with an OR of 2.6 (16).…”
Section: Risk Factors For Swi After Lower Limb Vascular Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Es könnte deshalb mit seiner Verwendung zur Reduktion des SSI-Risikos kommen. Die diesbezügliche Studienlage ist uneinheitlich [192][193][194][195][196][197][198][199][200][201]. Die WHO empfiehlt die Verwendung unabhängig von der Art der Operation [40], das CDC in der Viszeralchirurgie [202].…”
Section: Op-handschuheunclassified